Nanotube Combined with Roller Skater Rehabilitation Therapy in the Treatment of Knee Arthritis - Peng Sun (Advances in Materials Science and Engineering)
As a kind of nanotechnology, nanomaterials have made great progress in recent years, among which nanotube is one of the most representative new nanomaterials. Knee arthritis, as a degenerative bone disease, often occurs in the elderly. According to statistics, the incidence of knee arthritis in China is between 3 and 15 percent, among which the incidence of the elderly over 65 years old is as high as 68 percent. The purpose of this study is to explore the application effect of the rehabilitation therapy of nanotube combined with roller skater in the treatment of knee arthritis and promote the continuous improvement of clinical treatment effect of knee joint. In this study, by comparing the curative effect of the roller skates combined with nanotubes in the rehabilitation treatment group and the control group, the clinical treatment effects of the two groups were comprehensively evaluated and evaluating the comprehensive effects of nanotubes combined with roller skates from various angles of a comprehensive role of rehabilitation therapy in the treatment of knee osteoarthritis, to give full play to the advantages of nanotubes and rehabilitation therapy, promote the continuous improvement of treatment, and provide important guidance for the clinical treatment of knee arthritis, thereby improving the therapeutic effect. The results showed that the total effective dose was 82.61% in the control group and 97.83% in the observation group. Before and after the treatment, the therapeutic effect of the nanotube drug treatment group was improved by about 40%, and the therapeutic effect of the observation group of rehabilitation therapy with nanotube combined wheel athletes was increased by about 42%. It indicates that compared with the single treatment, the rehabilitation therapy of the nanotube combined with roller skater greatly improves the therapeutic effect of knee arthritis.